2016
DOI: 10.1590/18069657rbcs20150482
|View full text |Cite
|
Sign up to set email alerts
|

Reclamation of a Degraded Coal-Mining Area with Perennial Cover Crops

Abstract: Studies addressing the potential of grass roots in improving the structural quality of constructed minesoils are not frequent in the literature, although they are essential for understanding the re-establishment of soil functions in the environment. The objective of this study was to quantify the root attributes of the species Urochloa humidicola, Panicum maximum, and Urochloa brizantha and relate them to the physical properties of a constructed minesoil in reclamation of an area degraded by coal mining. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
6
0
1
Order By: Relevance
“…In reclaimed mine soil (RMS), examining the N dynamics can be especially informative for understanding recovery stresses restricting revegetation success. Soil horizons observed in RMS include A and/or C, and the B horizon cannot be formed because of the pedogenically young age (<10 years) of the constructed mine soils (Paulleto et al, 2016; Sencindiver & Ammons, 2000). However, the A horizon is quite thin and very different to the naturally formed soils (Cao et al, 2015; Shrestha & Lal, 2008; Wick et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In reclaimed mine soil (RMS), examining the N dynamics can be especially informative for understanding recovery stresses restricting revegetation success. Soil horizons observed in RMS include A and/or C, and the B horizon cannot be formed because of the pedogenically young age (<10 years) of the constructed mine soils (Paulleto et al, 2016; Sencindiver & Ammons, 2000). However, the A horizon is quite thin and very different to the naturally formed soils (Cao et al, 2015; Shrestha & Lal, 2008; Wick et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Drawing from the lessons of the occurrence of the devastation by coal mining on the ecosystem (in abandoned mined lands) and its subsequent revegetation from different regions of the world (Baig, 1992;Skousen et al, 1994;Sheoran et al, 2010;Yang et al, 2015;Pauletto et al, 2016;Buta et al, 2019), it was essential to examine how coal mining and its concomitant wastes have impacted the floral distribution in the Coal Camp/Ogbete area. We evaluated the plant diversity by (1) comparing the remnant species in the polluted coal site (IZ) and an undisturbed site (CZ) and by the assessment of the conservation status of the species within the study area.…”
Section: Introductionmentioning
confidence: 99%
“…This process is also capable of reducing erosion and protecting soil degradation [35]. However, possible occurrence is greatly decreased by cultivating legium cover crops (LCC) in early vegetation stages [36][37][38][39][40][41]. Based on this study, mine reclamation demonstrated the robust capacity to restore environmental degradation, but was unable to completely reform the depleted water resources.…”
Section: Introductionmentioning
confidence: 99%